Exploring the cancer-fighting properties of Catharanthus roseus: A natural powerhouse - Saima Sabrina; Sumita Rani Saha; Mohammad Kamruzzaman; Mohammod Johirul Islam (Plant Trends)
Catharanthus roseus contains high-value medicinal properties, which are widely used in treating diabetes, kidney, liver, cardiovascular, and other life-threatening diseases. This study aims to explore the potential properties of C. roseus that are used as cancer-fighting agents and update the prospects and pharmacological significance of C. roseus. This study highlights the screening of anticancer properties, in vitro phytochemicals, and pharmacological advancements through biological cell culture approaches. The updated findings further suggest the potential pathways of inhibiting cancer cells and prospect of the medicinal properties in healing life-threatening diseases. The findings together open new insights into using C. roseus properties in pharmaceutical significance, cancer treatment, and patient care. [Plant Trends 2024; 2(4.000): 108-115]